Analisis Sektor Usaha Kecil dan Menengah Sebagai Model Social Entrepreneurship Berbasis Ekonomi Kreatif (Studi Kasus pada Usaha Kuliner di Kecamatan Liliriaja Kabupaten Soppeng) - Ahmad, M. Ihsan Said; Hasan, Muhammad; Dinar, Muhammad; Permatasari, Diah; Inanna, Inanna (Journal of Economic Education and Entrepreneurship Studies, 2023)
In order to promote economic independence for communities, Social Entrepreneurship promotes social activities by encouraging the local community to become engaged in Small and Medium Enterprises (SMEs) as part of Social entrepreneurship. One way SMEs may ensure their own long-term success and expand their worldwide presence is by adopting a creative economy strategy from each industry. The goal is to ensure that small and medium-sized enterprises (SMEs) in Indonesia can thrive for the long term and ultimately become the backbone of the country's economy. The focus of this study is on small and medium-sized enterprises (SMEs) with the goal of incorporating them into the expanding field of social entrepreneurship within the context of the creative economy. Data is gathered via interviews, written records, and in-person observations (qualitative, interactive analysis approach). Based on these findings, it's clear that the local government actively promotes the growth of small and medium-sized enterprises (SMEs), notably those operating in the food service industry. Social entrepreneurship that relies on the creative economy is encouraged by both the government and large corporations like Google and Facebook because of its potential to boost the economy. Government and small and medium sized enterprises (SMEs) must be involved in order to ensure the long-term success of social entrepreneurship based on the creative economy.